(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
In Las cárceles clandestinas by Ana María Guadalupe Martínez and Nunca estuve sola by Nidia Díaz identities are negotiated based on the collectivity. However, these texts are also the search for individuality through the construction of female revolutionary identities. Dialogues simulate the negotiation of gender issues, national and family reconfigurations. This negotiation is made by two female revolutionary subjects from marginal spaces such as the clandestine jails in El Salvador. At the same time, this dialogue and the construction of revolutionary subjectivities are a defensive weapon against the torture suffered by the detainees.